2016
DOI: 10.1007/s12011-016-0650-2
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-Related Intestinal Mucositis in IBS-Like Patients: Laser Doppler Perfusion Imaging and Oral Mucosa Patch Test in Use

Abstract: Nickel (Ni) is often the trigger of irritable bowel syndrome (IBS)-like gastrointestinal disorders: its ingestion may cause allergic contact mucositis, identifiable by means of oral mucosa patch test (omPT). OmPT effectiveness has been proven, but it is still an operator-dependent method. Laser Doppler perfusion imaging (LDPI) was tested to support omPT in Ni allergic contact mucositis diagnosis. Group A: 22 patients with intestinal/systemic symptoms related to the ingestion of Ni-containing foods. Group B: 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…Symptoms triggered by the ingestion of Ni-rich foods in Ni-sensitive patients are mainly gastrointestinal, but they can also be systemic, involving the skin, the nervous and the reproductive system [49]. A low-Ni diet can improve symptoms in Ni-sensitive patients, though foods high in Ni are largely consumed, especially in the Mediterranean diet, such as tomatoes, cocoa, beans, mushrooms, broadleaf vegetables, and whole flour [47]. As Ni ePT is useful for the diagnosis of Ni ACD, so Ni omPT has proved to be a specific and sensitive tool for Ni ACM diagnosis [5,47,[49][50][51].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Symptoms triggered by the ingestion of Ni-rich foods in Ni-sensitive patients are mainly gastrointestinal, but they can also be systemic, involving the skin, the nervous and the reproductive system [49]. A low-Ni diet can improve symptoms in Ni-sensitive patients, though foods high in Ni are largely consumed, especially in the Mediterranean diet, such as tomatoes, cocoa, beans, mushrooms, broadleaf vegetables, and whole flour [47]. As Ni ePT is useful for the diagnosis of Ni ACD, so Ni omPT has proved to be a specific and sensitive tool for Ni ACM diagnosis [5,47,[49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal symptoms in endometriosis may also be related to IBS or IBS-like disorders [45]. Recent studies showed a higher prevalence of Ni skin allergy in women with endometriosis, as well as a possible Ni involvement in its etiopathogenesis [20,46,47]. On these bases, it is possible to hypothesize that an IBS-like disorder, such as Ni ACM, may be the cause or contributing factor of gastrointestinal symptoms in women with endometriosis.…”
Section: Gastrointestinal Disorders and Endometriosismentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnosis of dietary nickel sensitivity can be performed with a skin or oral mucosa patch test [110,112]. All patients reporting to a gastroenterology unit with IBS symptoms and suspected sensitivity to nickel containing foods had a positive response to an oral mucosa patch test characterized by local hyperemia and/or edema, compared to no response in a control group [113]. Beyond implementation of a low nickel diet, nutritional detoxification strategies have been proposed but currently lack clinical evidence [114].…”
Section: Nickel-related Intestinal Mucositismentioning
confidence: 99%
“…It is caused by the compression and thickening of the oral mucosal epithelium in response to mechanical stimulus, but it is not considered a pathological condition (Kumakura, Sakurai, Tahara, & Nakagawa, ). BMR can be easily distinguished from pathological conditions, such as lichen planus, leukoplakia, or allergic mucositis, which are associated with pain, erosions, ulcers, lace‐like leucoderma, or pseudomembrane formation (Borghini et al., ; Gupta, Gupta, Urs, & Singh, ; He et al., ). BMR observed along the occlusal plane was described as a sign of clenching, a characteristic of bruxism (Kampe, Tagdae, Bader, Edman, & Karlsson, ).…”
Section: Introductionmentioning
confidence: 99%